Analisa Efek Brand Image dan Brand Community terhadap Customer Loyalty pada Pelanggan Skin Game - Celica, Tasya; Rusdi, Farid (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2024)
The cosmetics industry has experienced an increase from year to year. To achieve this, the business strategy carried out is to build a brand image and form a brand community to maintain communication with customers. Loyal customers can have an interest in continuing to use the products offered continuously. Research was conducted to determine the influence of brand image and brand community on customer loyalty. This type of research is quantitative research. The research sample was 130 respondents. Data was obtained by distributing questionnaires via a Google Form link to Skin Game customers. The author's data analysis uses multiple linear regression. This research proves that there is a positive influence between brand image and customer loyalty, there is a positive influence between brand community on customer loyalty, and there is a positive influence between brand image and brand community simultaneously on customer loyalty. Skin games need to expand their brand so that it is easily recognized by the public and build a close brotherhood between community members, this is so that customer loyalty can increase. Industri kosmetik yang mengalami peningkatan dari tahjun ke tahun. Untuk mencapai ini, strategi bisnis yang dilakukan adalah dengan membangun brand image dan membentuk brand community untuk memelihara komunikasi dengan pelanggan. Pelanggan yang setia dapat memiliki minat untuk tetap menggunakan produk yang ditawarkan terus menerus. Penelitian dilakukan mengetahui pengaruh brand image dan brand community terhadap customer loyalty. Jenis penelitian ini adalah penelitian kuantitatif. Sample penelitian sebanyak 130 responden Data diperoleh dengan mendistribusi kuesioner melalui link google form kepada pelanggan Skin Game. Analisis data penulis menggunakan regresi linier berganda. Penelitin ini membuktkan bahwa adanya pengaruh positif antar brand image customer loyalty, adanya pengaruh positif antara brand community terhadap customer loyalty, serta adanya pengaruh positif antara brand image dan brand community secara bersamaan kepada customer loyalty. Skin game perlu memperluas mereknya agar mudah dikenal luas oleh masyarakat dan membangun persaudaraan yang erat antar anggota komunitas nya hal ini agar kesetiaan pelanggannya dapat meningkat.